Analisis Prediksi Penjualan Lampu Dengan Metode Svm Pada PT. Terang Abadi Raya - Sariayu, Vilomena; Sugiartawan, Putu (INFOTEKS (Information Technology, Computer and Sciences), 2022)
Predictive analytics is a type of data analysis technique used to make predictions about future events. In the Forecasting analysis of companies that buy and sell goods, it is necessary to facilitate the company's sales planning. In this study, an analysis of the Lamp Sales Forecast was carried out at PT. Great Eternal Light. Purpose The purpose of this study is to analyze the 2022 lamp sales forecast using the Support Vector Machine method. The results of the evaluation are carried out using the MAPE method to find out how much capacity the model has used to see the difference between the predicted and actual values. Haili test With MAPE 21.44 it can be said that the forecast model is quite good.